Impact of Health Education on Knowledge, Attitude, and Practice towards Human Papilloma Virus and its Vaccination - Santhosh Ramakrishna; Waseem Anjum; Veerabhadra Radhakrishna; Ravi Kudthni; Pooja Vishwanath (Perspectives In Medical Research)
Background: Despite the recommendation, the rate of Human Papilloma Virus (HPV) vaccine uptake is poor in developing countries. The possible reasons for this could be limited knowledge, poor acceptance, safety concerns, cost of the vaccine, and lack of awareness. Hence, a study was conducted to determine the effect of health education on knowledge, attitude, and practice toward HPV infection and its vaccination.Methods: An interventional study was conducted in the Tumkur district of India amongst female students studying in pre-university colleges. A questionnaire was provided to evaluate the knowledge, attitude, and practice about HPV infection and vaccination before and after health education.Results: After the health education, awareness about the effects of HPV and the mode of transmission of HPV increased from 62% to 71% (p<0.001) and 12% to 41% (p<0.001) respectively. Health education also increased knowledge about the availability of vaccination against HPV (34% to 87%; p<0.001), the population at risk for HPV infection (16% to 35%; p<0.001), the ideal age group for HPV vaccination (45% to 90%; p<0.001), and the overall knowledge score (5.6/17 to 12/17). Health education improved the willingness to pay for the vaccination from 34% to 56% (p<0.001) and the willingness to recommend others to vaccinate from 61% to 89% (p<0.001). Conclusion:The health education increased awareness about the symptomatology, mode of transmission, population-at-risk, and the effects of HPV infection. Health education also improved the willingness to pay for the vaccination and willingness to recommend others to vaccinate against HPV.